Agroecological estimation of the mineralogical composition of the soil - V I Savich (RUDN Journal of Agronomy and Animal Industries, 2016)
It is shown that the mineralogical composition of the soil is a factor when considering the lithology of soil at a lower hierarchical level. The mineralogical composition and determines the content ratio in the soil of nutrients and toxicants, ion exchange processes, soil resistance to degradation of soil fertility. It is the matrix of the formation of soil and regulates the transformation, migration and accumulation in soil of substances, energy and information of environmental and human impact.